2017
DOI: 10.3791/54798
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of an Aspirin-fumarate Prodrug that Inhibits NFκB Activity and Breast Cancer Stem Cells

Abstract: Inflammation is a cancer hallmark that underlies cancer incidence and promotion, and eventually progression to metastasis. Therefore, adding an anti-inflammatory drug to standard cancer regiments may improve patient outcome. One such drug, aspirin (acetylsalicylic acid, ASA), has been explored for cancer chemoprevention and anti-tumor activity. Besides inhibiting the cyclooxygenase 2-prostaglandin axis, ASA's anticancer activities have also been attributed to nuclear factor ĸB (NFĸB) inhibition. Because prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…ASA inhibits cyclooxygenase, which can remove hydroxy radical's production due to antioxidant and anti‐inflammatory properties of ASA . It also reduces the oxidative stress and inhibits NF‐κB by inhibiting TNF‐α . Furthermore, studies have confirmed the inhibition of lipid peroxidation and inhibit inflammatory mediators of IL‐4 and activator protein‐1 after aspirin administration .…”
Section: Discussionmentioning
confidence: 98%
“…ASA inhibits cyclooxygenase, which can remove hydroxy radical's production due to antioxidant and anti‐inflammatory properties of ASA . It also reduces the oxidative stress and inhibits NF‐κB by inhibiting TNF‐α . Furthermore, studies have confirmed the inhibition of lipid peroxidation and inhibit inflammatory mediators of IL‐4 and activator protein‐1 after aspirin administration .…”
Section: Discussionmentioning
confidence: 98%
“…Esophageal, prostate, breast, gastric, and gastro-intestinal cancers (153,(169)(170)(171)(172)(173) Downregulates atherothrombosis, inactivates platelet aggregation and cancer metastasis in esophageal and gastro-intestinal cancers. Inhibits angiogenesis in gastric cancer.…”
Section: Colorectal and Colon Cancers (166)mentioning
confidence: 99%
“…After its own activation, NF-kB can activate the transcription of various proinflammatory cytokines, chemokines and adhesion molecules. In cancer, a deregulated NF-kB pathway promotes tumor cell survival, proliferation, migration, invasion, angiogenesis, and resistance to therapy (169). Increased expression of NF-kB is associated with nasal polyposis (207).…”
Section: Regulation Of the Nf-kb Pathwaymentioning
confidence: 99%
“…These findings established a viable strategy for development of improved anti-inflammatory agents for chemoprevention and cancer treatment. 113 To improve drug efficacy and minimize toxicity, one study found that the fumarate-based ASA prodrug GTCpFE represents a prototype for development of novel anti-inflammatory and anti-CSC drugs for treatment of potentially aggressive breast cancers. 114…”
Section: Gtcpfementioning
confidence: 99%